2007
DOI: 10.1002/ange.200605019
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Micelles in Carbon Dioxide with Ionic‐Liquid Domains

Abstract: Das fluorierte Tensid N‐Ethylperfluoroctylsulfonamid kann in überkritischem CO2 inverse Micellen mit einer ionischen Flüssigkeit im Innern bilden. Diese Micellen können Salze solubilisieren, und mit HAuCl4 werden Goldnanopartikel (TEM‐Bild) gebildet. Das micellare System könnte einige der Vorteile von überkritischem CO2 und von ionischen Füssigkeiten als Solventien vereinen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 46 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…[9] Microemulsions with IL domains in organic solvents [10] or supercritical CO 2 continuous phases [11] have been studied. Bilayer membrane formation with synthetic glycolipids was also reported in ether-containing ILs.…”
mentioning
confidence: 99%
“…[9] Microemulsions with IL domains in organic solvents [10] or supercritical CO 2 continuous phases [11] have been studied. Bilayer membrane formation with synthetic glycolipids was also reported in ether-containing ILs.…”
mentioning
confidence: 99%
“…Liu et al [23] found that N-ethyl perfluorooctylsulfonamide (C 2 H 5 NHSO 2 C 8 F 17 ; N-EtFOSA) could form reverse microemulsions in supercritical CO 2 with 1, 1, 3, 3-tetramethylguanidinium ([(CH 3 ) 2 N] 2 C=NH 2 + ) acetate (TMGA), 1, 1, 3, 3-tetramethylguanidinium lactate (TMGL), and 1, 1, 3, 3-tetramethylguanidinium trifluoroacetate (TMGT) domains, and that the reverse microemulsions could solubilize salts, such as methyl orange, CoCl 2 , and HAuCl 4 . These new ionic liquid-in-SC CO 2 microemulsions systems may have certain advantages, especially when water-sensitive compounds are involved.…”
Section: Ionic Liquid-in-sc Co 2 Microemulsionsmentioning
confidence: 98%
“…These features favor the applications of scCO 2 as an extractant of organic substances from IL media after synthetic processes [14][15][16][17], with the ensuing benefit of very low cross-contamination of the extracted components with the IL. Other examples of applications combining an IL and scCO 2 include, e.g., the IL-in-scCO 2 microemulsions [18,19], the use of CO 2 as a phase separation switch in IL-organic [20] or IL-water [21] systems, or the reversible ILs as a class of switchable solvents [22,23].…”
Section: Introductionmentioning
confidence: 99%